Hospital admissions from a pediatric HIV care and treatment program in Malawi. Issue 1 (December 2016) - Nosek, Carl; Buck, W.; Caviness, Alison; Foust, Abbie; Nyondo, Yewo; Bottomani, Madalitso; Kazembe, Peter
Abstract Background The scale up of pediatric antiretroviral treatment programs across Sub-Saharan Africa over the last decade has brought increasing numbers of children into HIV care. This patient population requiring life-long care presents new challenges in the outpatient and inpatient settings. We sought to describe hospitalizations from a large pediatric HIV treatment facility to better understand the scope of the situation and identify areas for improved care delivery. Methods We conducted a retrospective case series of all HIV-infected and exposed patients <18 years enrolled at Baylor College of Medicine Children's Foundation Malawi, from October 2004-October 2010. Patients admitted to the hospital on or after the day of enrollment were included. Data were extracted from electronic clinic records. Analysis was done at the patient and admission level, as some patients had multiple admissions. Results Of 5062 patients enrolled in care, 877 (17.3 %) had 1137 admissions at median age 24 months (IQR: 12–62). 191 (21.8 %) patients had multiple admissions. A high proportion of admissions occurred in patients under two years (49.4 %), those within one month of clinic enrollment (32.9 %), those with severe immune suppression (44.0 %), and those not on ART (48.5 %). The frequency of primary admission diagnoses varied across these same variables, with malnutrition, pneumonia, and malaria being the most common. Conclusions Illness requiring hospitalization is common in HIV-infected and exposed children and these results reinforce the need for a comprehensive care package with special attention to nutrition. Strengthened programs for malaria prevention and expanded access to pneumococcal vaccine are also needed. The high burden of admissions in children under 24 months and those newly enrolled in care suggests a need for continued improvement of early infant diagnosis and provider-initiated testing programs to link patients to care before they are symptomatic. Similarly, the high proportion of admissions in those not yet started on ART emphasizes the importance of rapid initiation of ART for eligible pediatric patients.